2022
DOI: 10.1016/j.jare.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

An altered microbiota pattern precedes Type 2 diabetes mellitus development: From the CORDIOPREV study

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Several human studies have reported a cross-sectional association of the microbiota with type 2 diabetes [ 3 , 5 , 6 ]. Recently, two European cohorts with relatively moderate sample sizes ( n = 273 and 608, respectively) examined the prospective association of the gut microbiota with type 2 diabetes or glycaemic traits [ 7 , 8 ]. However, the results from these previous studies were inconsistent, and evidence from large prospective cohorts is still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several human studies have reported a cross-sectional association of the microbiota with type 2 diabetes [ 3 , 5 , 6 ]. Recently, two European cohorts with relatively moderate sample sizes ( n = 273 and 608, respectively) examined the prospective association of the gut microbiota with type 2 diabetes or glycaemic traits [ 7 , 8 ]. However, the results from these previous studies were inconsistent, and evidence from large prospective cohorts is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota-targeted dietary intervention is a promising and cost-efficient method to reduce disease risk [ 12 , 13 ]. However, neither of the prospective studies [ 7 , 8 ] evaluated the association of dietary or lifestyle factors with gut microbial genera that were specifically associated with type 2 diabetes or glycaemic traits.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the type of intervention and individual factors influence the outcome of weight-reductions means [ 2 , 3 ]. Among the individual factors, the intestinal microbiota is a highly interesting data source that might yield such predictive variables, since it has been shown that obesity and metabolic processes and disease are affected by individual microbiota patterns [ 6 , 7 , 8 , 13 , 14 , 15 ]. Here, we show for the first time that defined microbiota patterns can be related to individual weight loss success following a nonsurgical, multidisciplinary weight loss program performed over one year.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, gut microbiota dysbiosis has also been shown to be associated with the development of T2DM. , Wu et al discovered that the abundance of certain butyrate-producing bacteria, such as Clostridium , Oscillibacter , and Alistipes , was reduced both in prediabetes and T2DM individuals . Furthermore, people with high abundance of Prevotella and Granulicatella genera were at higher risk of T2DM, and the combination of microbiome data and clinical parameters could more accurately predict the development of T2DM . It is worth noting that a growing number of studies have explored the mechanisms by which the gut microbiota plays a role in DM, especially T1DM and T2DM (Figure ).…”
Section: Effects Of the Gut Microbiota On Dmmentioning
confidence: 99%
“…30 Furthermore, people with high abundance of Prevotella and Granulicatella genera were at higher risk of T2DM, and the combination of microbiome data and clinical parameters could more accurately predict the development of T2DM. 31 It is worth noting that a growing number of studies have explored the mechanisms by which the gut microbiota plays a role in DM, especially T1DM and T2DM (Figure 1). Molecular Mechanisms for T1DM.…”
Section: ■ Effects Of the Gut Microbiota On Dmmentioning
confidence: 99%